Retrometabolic drug design and targeting - Bodor, Nicholas; Buchwald, Peter (Oxford : Wiley-Blackwell, 2012)
This book provides researchers in drug discovery and design with complete guidance on how to use retrometabolic approaches to develop safe, effective, and targeted drug therapies. Written by pioneers in soft drugs and retrometabolics, the book brings together for the first time a wealth of information from across the literature, offering a single source of valuable ideas, methods, and references to the problems of drug design, optimization, stability, side effects, and toxicity. Authoritative coverage includes both important fundamentals and practical examples illustrating applications in drug design.
Includes bibliographical references and index.
Print version record.
Keywords: Drugs -- Design; Drugs -- Design; Electronic books